Persaingan Bisnis Dalam Novel Gadis Kretek Karya Ratih Kumala - Freedianingtias Subekti; Sophia Puspita Ningrum; Eva Dwi Kurniawan (Jurnal Manajemen Kreatif dan Inovasi, 2024)
This study aims to determine the Business Competition in the Novel Gadis Kretek by Ratih Kumala. The novel was published in 2012. The data collection techniques used are reading techniques and analyzing techniques. The method used in this research is qualitative method and descriptive analysis method. The source of data used in this research is the literary work of the novel Gadis Kretek by Ratih Kumala. Based on the results of the study, it can be concluded that there are factors that affect business competition in the Gadis Kretek Novel, namely industry competition, bargaining power of buyers, and the threat of substitute products.